Tren Flavor Produk Pangan di Indonesia, Malaysia, Filipina, dan Thailand - Sjahwil, Lisa Norisza; Andarwulan, Nuri; Hariyadi, Purwiyatno (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
This study aimed to determine avor trend of food products launched within major ASEAN countries of Indonesia, Malaysia, Filipina and Thailand in 2006 – 2010 where their domestic market continues to grow. Materials used in this study were secondary data-subscribed via Mintel, Euromoni- tor, Datamonitor and other literatures associated with launches, demographic, and culinary information. Product launches positively correlate with Gross Domestic Product (GDP) (R2=0.796). The ve common food categories of food products launched were non-alcoholic beverages, bakery, sauce and seasonings, snacks and dairy products. Domestic ranking (rank 1–4) of these food categories was slightly difference for each country. The 5th rank for each country was different i.e. Malaysia with dairy products, Indonesia with baby foods, Philippines with sugar and gum confectionery and Thailand with meals and meal centers. The difference was mostly related to social-economy factor. Flavor trends in non-alcoholic beverages were fruits and chocolate; bakery were chocolate, strawberry, vanilla and dairy such as cheese, milk and but- ter; sauce and seasonings were chili-pepper, soy sauce, tomato, barbeque; snacks were cheese, barbeque, spice/spicy and dairy products were chocolate, strawberry, vanilla.